2008
DOI: 10.1128/jvi.00812-08
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of Foamy Retrovirus Gag Contains Determinants for Encapsidation of Pol Protein into Virions

Abstract: Foamy viruses (FV) differ from orthoretroviruses in many aspects of their replication cycle. A major difference is in the mode of Pol expression, regulation, and encapsidation into virions. Orthoretroviruses synthesize Pol as a Gag-Pol fusion protein so that Pol is encapsidated into virus particles through Gag assembly domains. However, as FV express Pol independently of Gag from a spliced mRNA, packaging occurs through a distinct mechanism. FV genomic RNA contains cis-acting sequences that are required for Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
63
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 30 publications
5
63
1
Order By: Relevance
“…However, it appears to be linked to the packaging of another essential component of the infectious viral particle, the viral genomic RNA (29,32). Current data suggest that protein-RNA interaction of both Gag and Pol with viral genomic RNA as well as protein-protein interactions between Gag and Pol are involved in the assembly process (14,21,29).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it appears to be linked to the packaging of another essential component of the infectious viral particle, the viral genomic RNA (29,32). Current data suggest that protein-RNA interaction of both Gag and Pol with viral genomic RNA as well as protein-protein interactions between Gag and Pol are involved in the assembly process (14,21,29).…”
mentioning
confidence: 99%
“…However, Pol expression is not fully Gag independent as mutations introduced at the C terminus of Gag influence the levels of spliced pol mRNA (21). As a consequence of separate Pol expression, FVs require a strategy different from that of orthoretroviruses to ensure Pol particle incorporation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is assumed that the vRNA serves as a bridging molecule between Gag and Pol during assembly. There are conflicting results related to the requirement of additional protein-protein interactions between both proteins for PFV Pol incorporation (11)(12)(13). Interestingly, only the unprocessed Pol precursor protein appears to be efficiently packaged into assembling PFV particles (9,14).…”
mentioning
confidence: 96%
“…Recently, however, it was shown that Gag, too, contains C-terminal determinants that facilitate encapsidation of Pol into the virions. 12 This independent expression of Pol from a spliced mRNA may be an advantage for vector development, as a vector produced from three separate plasmids encoding each of the structural genes is less likely to undergo recombination. Foamy virus capsids are restricted to the cytoplasm in the absence of its cognate envelope protein and, thus, particles are not released into the supernatant in the absence of it or in the provision of a different envelope.…”
mentioning
confidence: 99%